Clinical Holistic Medicine: Treatment of Physical Health Problems Without a Known Cause, Exemplified by Hypertension and Tinnitus - Søren Ventegodt; Mohammed Morad; Isack Kandel; Joav Merrick (The Scientific World Journal)
In the medical clinic, we often face health problems that have no known cause, even after a thorough examination. Biomedicine is often unable to find a cure in these situations, leaving the problem unsolved or leaving the patient on a palliative pharmaceutical cure, which is often for a lifetime. In this case, consciousness-based, holistic medicine could be an alternative. Using the theories and tools of holistic medicine wisely, the physician can often provide treatment for the patient. The toolbox of holistic medicine makes it possible to work on everybody because there is always something related to the patients quality of life that can be improved: his love, his purpose of life, and the way he uses his talents, his mind, his feelings, his body, and his sexuality. For treatment in holistic medicine, it really does not matter as much that you cannot give the patient a precise medical diagnosis, because you can always work on the patient with the intention of healing his or her whole life and existence. It is quite a paradox that many of these diseases can be understood on the level of the individual patient at the same moment that the patient is cured; many of these diseases seem to be clearly related to the repression of the individual character, as stressed already by Hippocrates. So if you simply start working with the patient to help him confront old existential pain and coach him in his personal development of his life by intensifying its meaning and purpose, the symptoms very often simply disappear. The toolbox of holistic medicine also seems relevant to even difficult, neurotic, psychosomatic, and hypochondriac patients. Believing in the treatment and not giving up on your patient, and moving forward in the treatment with the patient himself is the ultimate goal, even when you yourself do not understand the mechanism fully. This will force you to develop your own competence and is, in essence, what makes an outstanding holistic physician.